2006
DOI: 10.1211/jpp.58.9.0006
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific accumulation of the cancer preventive dietary polyphenol ellagic acid in epithelial cells of the aerodigestive tract

Abstract: Ellagic acid (EA), a polyphenol present in berries, has been demonstrated to prevent oesophageal and colon cancer in animals. To better understand the site-specificity of these effects, we studied the accumulation and transport of [14C]EA in rat aerodigestive epithelial cells in-vivo and in cultured human cells. When [14C]EA was administered to rats by gavage, a high content of EA was found in the oesophagus and small intestine at 0.5 h after oral administration and in the colon at 12 h, with very low amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…However, although EA solubility greatly increased at pH over 7.5, this did not match in the human study where higher EA absorption at longer post-ingestion times was only observed in a few cases, especially after the intake of PE-1. This supported the idea that EA intestinal absorption was hampered and/or saturated, which was in agreement with preclinical studies where EA showed a limited transcellular transport (Whitley, Sweet, & Walle, 2006). In addition, this saturation phenomenon is also sustained by in vitro studies that have also reported the efficient EA transport by intestinal organic anion transporters (OATs) with a very high affinity for hOAT1 (Whitley, Sweet, & Walle, 2005), which resulted inhibited at EA concentrations (5-25 µM) that can be reached in the human colonic mucosa (Núñez-Sánchez et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, although EA solubility greatly increased at pH over 7.5, this did not match in the human study where higher EA absorption at longer post-ingestion times was only observed in a few cases, especially after the intake of PE-1. This supported the idea that EA intestinal absorption was hampered and/or saturated, which was in agreement with preclinical studies where EA showed a limited transcellular transport (Whitley, Sweet, & Walle, 2006). In addition, this saturation phenomenon is also sustained by in vitro studies that have also reported the efficient EA transport by intestinal organic anion transporters (OATs) with a very high affinity for hOAT1 (Whitley, Sweet, & Walle, 2005), which resulted inhibited at EA concentrations (5-25 µM) that can be reached in the human colonic mucosa (Núñez-Sánchez et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…This low solubility is partly due to its high degree of crystallinity, which is directly related to its planar and symmetrical structure and the hydrogen-bonding network formed in the crystal (Li, Harich, Wegiel, Taylor, & Edgara, 2013). Indeed, previous animal studies identified the low solubility of EA in aqueous media as a major drawback in EA absorption (Daniel, Ratnayake, Kinstle, & Stoner, 1991) as well as its ability to bind the intestinal epithelium (Whitley, Sweet, & Walle, 2006). In the present study, we confirmed the very low recovery of free EA under in vitro gastric conditions, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…85 In addiction, several cancer preventive PPs selectively accumulate in the epithelial cells of the upper digestive tract of rats, with an ATP-and Na + -dependent organic anion transport mechanism. 86 Epidemiological study results are consistent with experimental studies. Specifically, a recent South African retrospective study reported that diets poor in fruit and vegetables, with consequent low PP content, are responsible for 7% and 10% of oesophageal cancers among females and males, respectively.…”
Section: Polyphenols and Oral Cancersupporting
confidence: 83%
“…1) [12 -14]. EA and urolithins can accumulate in the intestine and prostate [15,16]. ETs, EA and urolithin-A exhibit cancer chemopreventive activities in various cell and animal models [16 -19] but the antiproliferative activity of EA metabolites in colon cells has not been studied, and the molecular mechanisms involved have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%